2022
DOI: 10.1001/jama.2022.1190
|View full text |Cite
|
Sign up to set email alerts
|

Association of SARS-CoV-2 Infection With Serious Maternal Morbidity and Mortality From Obstetric Complications

Abstract: IMPORTANCEIt remains unknown whether SARS-CoV-2 infection specifically increases the risk of serious obstetric morbidity.OBJECTIVE To evaluate the association of SARS-CoV-2 infection with serious maternal morbidity or mortality from common obstetric complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
157
3
3

Year Published

2022
2022
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(195 citation statements)
references
References 26 publications
9
157
3
3
Order By: Relevance
“…Apgar score < 7 at 5' Recent studies have shown that pregnant women are more likely to develop asymptomatic SARS-COV-2 infections than non-pregnant women, but this does not exempt them from experiencing obstetric and neonatal complications due to this infection [5,6,14]. The most frequent symptoms reported in this study were coryza, cough, loss of smell and taste, headache, and fever, corroborating the findings of Allotey et al, who reported fever and cough [7].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Apgar score < 7 at 5' Recent studies have shown that pregnant women are more likely to develop asymptomatic SARS-COV-2 infections than non-pregnant women, but this does not exempt them from experiencing obstetric and neonatal complications due to this infection [5,6,14]. The most frequent symptoms reported in this study were coryza, cough, loss of smell and taste, headache, and fever, corroborating the findings of Allotey et al, who reported fever and cough [7].…”
Section: Discussionsupporting
confidence: 87%
“…It is important to note that the frequency of unfavorable outcomes was higher in the group of patients exposed to the virus, who showed a higher incidence of cesarean section, premature delivery, admission to NICU, need for resuscitation, neonatal jaundice, and need for phototherapy, which despite not being statistically significant, corroborates the literature, similar to the results of Metz et al, Chmielewska et al, Litman et al, and Chinn et al, which showed higher rates of maternal death, clinical complications, fetal loss, ectopic pregnancy, maternal depression and premature birth associated to SARS-CoV-2 infection [4,5,8,19].…”
Section: Plos Onesupporting
confidence: 88%
See 1 more Smart Citation
“…An increasing body of evidence demonstrates that pregnant persons with SARS-CoV-2 infection are at higher risk of severe COVID-19 including hospitalization, intensive care, mechanical ventilation, and death 1-3 . Furthermore, adverse perinatal outcomes such as increased risk of preterm birth, preeclampsia, and stillbirth have been observed with SARS-CoV-2 infection in pregnancy, particularly in the setting of moderate-severe disease 1 3-6 . COVID-19 vaccines have been granted Emergency Use Authorization by the U.S. Food and Drug Administration, although pregnant persons were excluded from published phase three vaccine trials.…”
Section: Introductionmentioning
confidence: 99%
“…Wir haben in unserem Update wiederholt auf die Gefahren einer COVID-19-Erkrankung in der Schwangerschaft hingewiesen. Eine retrospektive Kohortenstudie erhob mütterliche und neonatale Sterbefälle, die Inzidenz hypertensiver Entgleisungen, postpartale Blutungen, Infektionen während und unmittelbar nach Schwangerschaft bei 14.104 PCR-positiven Patientinnen aus 17 US-Spitälern und verglich diese mit COVID-negativen Schwangeren [ 8 ]. Das Risiko, zu sterben, eine hypertensive Entgleisung zu erfahren, postpartal stärker zu bluten oder eine Infektion zu bekommen, war für infizierte Mütter signifikant erhöht.…”
unclassified